NEW SILK ROAD: OPPORTUNITIES AND THREATS FOR CENTRAL ASIA (A VIEW FROM KAZAKHSTAN) - AUBAKIROVA, Amina; UMIRZAKOV, Samazhan; AITENOV, Nurakhmet (CENTRAL ASIA AND THE CAUCASUS, 2017)
In connection with the Chinese project One Belt, One Road, the article deals with geopolitical aspects of the ways of its implementation. The focus is on the participation of Kazakhstan and the post-Soviet countries of Transcaucasia and Central Asia in the project. Highlighted are the geopolitical interests of Russia and China, Turkey and Iran, as well as the extra-regional powers—the European Union and the United States. An attempt is made to outline new threats and risks for the region in connection with the building of the New Silk Road. Contributors represent their point of view mainly through the prism of the interests of Kazakhstan. After the disintegration of the Soviet Union, the geopolitical position of the republics of Central Asia and Kazakhstan proved to be extremely difficult. All of them are located in the depths of the largest continent—Eurasia, away from sea routes. In the last two centuries, being part of the Russian Empire and then the U.S.S.R., these republics were perceived by the world community as the backward provinces of the two empires. For many centuries, the region was situated along the Great Silk Road and served as a link between the West and East. Many medieval cities in Southern Kazakhstan and Central Asia emerged due to its existence. Today, the modern tourist value of these cities is, in many respects, connected with preserved objects of the Silk Road. The obsolescence of the region as a link between East and West was caused by the opening of maritime communications. Additionally, the rupture of these links was influenced by ideological reasons from the Russian Empire and later the Soviet Union. Despite the disruption of ties with the outside world, the region maintained its distinctive identity during the Soviet period. In recent times, being positioned between two strong states—Russia and China—and the Islamic world, particularly Turkey and Iran, post-Soviet Central Asia has experienced significant political and civilizational influence from these countries. The realization of membership in the Turkic-Muslim culture, the influence of China, strong post-Soviet traditions, and the search for national identity all contribute to a complex fusion in the region's modern history. The revival of the Great Silk Road raises questions about the region's place in the world community. Will Central Asia remain within the post-Soviet space under the strong influence of Russia, become a commodity appendage of China, or endeavor to reconnect with its Turko-Muslim roots? These questions will shape the future trajectory of the region and its geopolitical significance.